Self-biasing multiple-gated-transistors method in designing low-noise amplifier and third-order chebyshev filter - Abbasi, Arash (2015)
Analog filters and low noise amplifiers (LNAs) are extensively employed in the receiver front-end structure of the CMOS radio frequency (RF) applications. One of the analog filters usually employed in CMOS RF is Gm-C filter which consists of transconductor (Gm or OTA) block and capacitor (C). The OTA is the main building block of the Gm-C filter that the characteristics of the Gm-C filter is related to its performance. While several techniques are reported to design OTA, its major limitation is its poor linearity and complexity of the design. In addition, the LNA is modified to achieve sufficient linearity, reduce complexity of the design and lower noise figure (NF) to suppress the noise from the first stage of the receiver. In this dissertation, a self-biasing multiple-gated-transistors (MGTR) method is modified to improve the linearity of the OTA and LNA. Self-biasing reduce the complexity of the design and number of components. The basic concept of the MGTR method is utilizing two transistors in order to remove the third-order harmonics of each other. Each of these transistors must be biased in different region. Thus, two external biasing is needed. However, the number of external biasing is reduced by self-biasing modification. The modified method is used to modify an OTA for the Gm-C filter. Then, the Gm-C filter is used by third-order Chebyshev filter to prepare the requirements of direct conversion receiver for digital television (DTV). The modified OTA is designed in 90 nm CMOS technology. The simulation result with two-tone test at 100 MHz center frequency shows that the third-order Chebyshev filter with modified OTA has 8 dBm Input-referred Third-Order Intercept Point (IIP3) improvement compared with the third-order Chebyshev filter with single-gate OTA. The third-order Chebyshev filter with modified OTA is operating between 50-200 MHz cutoff frequencies. Moreover, it achieves maximum NF of 13.5 dB and maximum IIP3 of approximately 17.3 dBm at 100 MHz, whereas consuming 18 mA with 1.2 V supply voltage. Furthermore, the modified LNA is operating between 900-2400 MHz cutoff frequencies. The simulation result with two-tone test at 2.1 GHz sample center frequency shows that the modified LNA has 10 IIP3 improvement compared with a single-gate LNA. The modified LNA achieves maximum NF of 1.9 dB, 9 dB Gain and maximum IIP3 of approximately 13.5 dBm, whereas consuming 3.9 mA with 2 V supply voltage.